Penggunaan Alat Kontrasepsi Wanita Usia Subur - Andhie Lestari, Yogi (Journal of Fundus, 2024)
Family planning is an action that helps married couples to regulate pregnancy intervals, determine the number of children, and prevent unwanted pregnancies. Family planning methods in the government programme based on the protection period are Long-Term Contraceptive Methods and non-Long-Term Contraceptive Methods. From the results of simple interviews with 10 women of childbearing age in Karangtawang village, Nusawungu sub-district, Cilacap district, Central Java, 70% stated that they used non- Long-Term Contraceptive methods, and 30% used Long-Term Contraceptive. From the above results, the researcher was interested in the use of contraceptive in women of childbearing age in Karangtawang village, Cilacap. This study used an observational survey design with a cross sectional time approach. This research was conducted in March 2024 in Karangtawang village Cilacap. The sample obtained was 228 people. Data analysis used univariate analysis and bivariate analysis. The results showed that there were significant differences in contraceptive use based on characteristics and income with a p value of <0.05. It is necessary to conduct a broader analysis by including factors that influence the use of non Long-Term Contraceptive Methods